Analisis Implementasi Kebijakan Pelayanan Administrasi (PATEN) di Kecamatan Tempe Kabupaten Wajo - Andi Amalia Ramdani; Muktamir Usman; Supris Musafir (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
One of the government's steps to achieve quality public services is the implementation of Regional Regulation of Domestic Affairs No. 4 of 2010 concerning Guidelines for Integrated Regional Administration Services (PATEN). The report of the Minister of Home Affairs No. 318/312/PUM dated February 28, 2011, outlines the implementation of Integrated Regional Administration Services (PATEN). PATEN is carried out with the aim of making cities the center of community services and serving as service points for subdistrict offices within the regencies/cities, ensuring that the geographical areas can be served more effectively and efficiently. This study is a qualitative research aimed at providing a general or descriptive overview of the researched topic. To offer a general or descriptive overview, the researcher relies on field data. The findings of this study solely describe or frame in-depth interviews with research subjects to provide a clear understanding of the analysis of the implementation of Integrated Administration Policy in Tempe Subdistrict, Wajo Regency. With the steps that have been taken, it is expected that PATEN in Tempe Subdistrict can operate more effectively, efficiently, and transparently, in line with its objective of delivering optimal services to the community.